2005
DOI: 10.1038/sj.jp.7211289
|View full text |Cite
|
Sign up to set email alerts
|

Heat Loss Prevention for Preterm Infants in the Delivery Room

Abstract: OBJECTIVE:Preterm infants are prone to hypothermia immediately following birth. Among other factors, excessive evaporative heat loss and the relatively cool ambient temperature of the delivery room may be important contributors. Most infants <29 weeks gestation had temperatures <36.41C on admission to our neonatal unit (NICU). Therefore we conducted a randomized, controlled trial to evaluate the effect of placing these infants in polyurethane bags in the delivery room to prevent heat loss and reduce the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
133
1
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 19 publications
8
133
1
10
Order By: Relevance
“…Over two-thirds of ELBW infants are admitted to neonatal intensive care units (NICUs) with temperatures that would be considered hypothermic. 10 Mechanisms of preventing heat loss Mechanisms to prevent heat loss in newborn infants include the most basic manipulation of the environment to the most sophisticated and highly technical interventions. First and foremost, the general environmental temperature must be addressed.…”
Section: Hypothermiamentioning
confidence: 99%
See 1 more Smart Citation
“…Over two-thirds of ELBW infants are admitted to neonatal intensive care units (NICUs) with temperatures that would be considered hypothermic. 10 Mechanisms of preventing heat loss Mechanisms to prevent heat loss in newborn infants include the most basic manipulation of the environment to the most sophisticated and highly technical interventions. First and foremost, the general environmental temperature must be addressed.…”
Section: Hypothermiamentioning
confidence: 99%
“…Cold delivery rooms (delivery rooms maintained at a temperature <26 1C) have been associated with colder admission temperatures in the NICU for ELBW infants. 10 Raising delivery room temperature may be one of the most direct ways that hypothermia and cold stress can be addressed.…”
Section: Hypothermiamentioning
confidence: 99%
“…2 Despite World Health Organization 3 recommendations to keep the delivery room temperature at least 251C, it is common for extremely low birth weight (ELBW) infants to be exposed to cold environments in the delivery room after birth and through stabilization. In the past, we found delivery room temperatures to be as low as 18.91C, 4 despite attempts to keep delivery room temperatures at least 261C. Cold stress is more likely during the birth process and during stabilization in the delivery room because the infant is delivered from the warm intrauterine environment to the cold, drafty environment of the delivery room.…”
Section: Introductionmentioning
confidence: 98%
“…In three randomized controlled trials (RCT), 4,6,7 we have shown that polyethylene wrap or polyurethane bags prevented heat loss in preterm infants less than 29-weeks gestation in the delivery room. In all studies, the preterm infant was delivered and placed on the radiant warmer for resuscitation, then intervention group infants were immediately covered with polyethylene wrap or polyurethane bags from the neck down while still wet with amniotic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been superseded by the technique of wrapping preterm babies in food or hospital standard polythene bags to prevent evaporative heat loss while permitting radiant warming. [9][10][11][12][13][14] Despite the relative success of wrapping babies in polythene bags, some are still hypothermic. In the HeLP study of babies <28 weeks wrapped in polythene bags, the mean rectal admission temperature was 36.5 1C (s.d., 0.8 1C).…”
Section: Introductionmentioning
confidence: 99%